Розв’язність нелокальної крайової задачі для системи диференціально-операторних рівнянь у шкалі просторів Соболєва та уточненій шкалі - Ільків, В.С.; Страп, Н.І. (Український математичний журнал, 2015)
Изучена разрешимость нелокальной краевой задачи с одним параметром для системы дифференциально-операторных уравнений в шкале пространств Соболева функций многих комплексных переменных и в шкале пространств Хермандера, которые образуют уточненную шкалу Соболева. Доказаны теоремы метрического характера об оценках снизу малых знаменателей, появившихся при построении решения исследуемой задачи, из которых следуют условия ее однозначной разрешимости для почти всех векторов, составленных из коэффициентов уравнения и параметра нелокальных условий. The paper is devoted to the investigation of the solvability of nonlocal boundary-value problem with one parameter for a system of differential-operator equations in the Sobolev scale of spaces of functions of many complex variables and in the scale of Hormander of spaces which form a refined Sobolev scale. By using the metric approach, we prove the theorems ¨ on lower estimates of small denominators appearing in the construction of solutions of the analyzed problem. They imply the unique solvability of the problem for almost all vectors formed by the coefficients of the equation and the parameter of nonlocal conditions.